Analyzing AbrB-Knockout Effects through Genome and Transcriptome Sequencing of Bacillus licheniformis DW2 - Shu, Cheng-Cheng; Wang, Dong; Guo, Jing; Song, Jia-Ming; Chen, Shou-Wen; Chen, Ling-Ling; Gao, Jun-Xiang (Frontiers in Microbiology, 2018)
As an industrial bacterium, Baccillus licheniformis DW2 produces bacitracin which is an important antibiotic for many pathogenic microorganisms. Our previous study showed AbrB-knockout could significantly increase the production of bacitracin. Accordingly, it was meaningful to understand its genome features, expression differences between wild and AbrB-knockout (ΔAbrB) strains, and the regulation of bacitracin biosynthesis. Here, we sequenced, de novo assembled and annotated its genome, and also sequenced the transcriptomes in three growth phases. The genome of DW2 contained a DNA molecule of 4,468,952 bp with 45.93% GC content and 4,717 protein coding genes. The transcriptome reads were mapped to the assembled genome, and obtained 4,102 ~ 4,536 expressed genes from different samples. We investigated transcription changes in B. licheniformis DW2 and showed that ΔAbrB caused hundreds of genes up-regulation and down-regulation in different growth phases. We identified a complete bacitracin synthetase gene cluster, including the location and length of bacABC, bcrABC and bacT, as well as their arrangement. The gene cluster bcrABC were significantly up-regulated in ΔAbrB strain, which supported the hypothesis in previous study of bcrABC transporting bacitracin out of the cell to avoid self-intoxication, and was consistent with the previous experimental result that ΔAbrB could yield more bacitracin. This study provided a high quality reference genome for B. licheniformis DW2, and the transcriptome data depicted global alterations across two strains and three phases offered an understanding of AbrB regulation and bacitracin biosynthesis through gene expression.